Efeitos do flavonoide luteolina na sinalização redox de células do endotélio venoso de ratos - Assunção, Henrique Charlanti Reis [UNIFESP] (2021)
The endothelium plays an essential role in vascular physiology, acting through a series of vasorelaxants substances such as nitric oxide (NO• ), and vasoconstrictors substances, such as the reactive oxygen species (ROS) radical superoxide (O2 •− ). In the vascular system, the main mechanism of O2 •− is to decrease in the bioavailability of NO• , through the chemical reaction between the two species. The product of this reaction is the peroxynitrite anion (ONOO¯), which can promote molecular changes such as protein nitration. The imbalance between these and other redox species is known as oxidative stress, harmful to the organism. Because of this antioxidant substances such as flavonoids can be beneficial in helping the organism to regulate this imbalance. Redox signaling is still poorly understood in the venous endothelium, an environment little studied in general. This work aimed to evaluate the action of the flavonoid luteolin in the redox signaling of rat vena cava endothelial cells, specifically the production of NO• , ROS and nitrotyrosine residues. To do so, immortalized cultures of endothelium previously established by our group were used. The evaluation of cytotoxicity was performed using the automated cell counter LUNA-FLTM, which demonstrated the absence of cytotoxic effects at the three studied concentrations [10, 20 and 50 μmol/L]. Experiments done in confocal microscopy with fluorescent probes demonstrated that luteolin was able to promote in 10 min a consistent increase in NO• production and a significant reduction in ROS by venous endothelial cells, in the three concentrations studied. NO• production was also measured in a spectrofluorometer, where 10 min of exposure to 50 μmol/L of luteolin induced an increase in NO• generation compared to basal, an effect not observed in lower concentrations. Also in spectrofluorometer, it was observed that exposure to luteolin for 24 h was able to significantly reduce the production of ROS in relation to basal, with effects comparable to TEMPOL, mimetic of the endogenous enzyme with antioxidant activity, superoxide dismutase. The presence of nitrated tyrosine residues was determined by immunofluorescence assays and demonstrated that exposure to luteolin for 10 min was able to significantly reduce the presence of nitrotyrosine residues, in the three concentrations studied, without differences between groups. In conclusion, luteolin is effective in reducing ROS and increasing the bioavailability of NO• in venous endothelium culture. In addition, these results also suggest that this change may decrease the amount of nitrated proteins, decreasing the impact of this type of molecular change. These findings indicate a possible future application of this flavonoid as a protective agent, improving endothelial function in several circulatory disorders related to venous insufficiency.